2018
DOI: 10.1371/journal.pone.0198333
|View full text |Cite
|
Sign up to set email alerts
|

Literary evidence for taro in the ancient Mediterranean: A chronology of names and uses in a multilingual world

Abstract: Taro, Colocasia esculenta (L.) Schott, is a vegetable and starchy root crop cultivated in Asia, Oceania, the Americas, Africa, and the Mediterranean. Very little is known about its early history in the Mediterranean, which previous authors have sought to trace through Classical (Greek and Latin) texts that record the name colocasia (including cognates) from the 3rd century BC onwards. In ancient literature, however, this name also refers to the sacred lotus, Nelumbo nucifera Gaertn. and its edible rhizome. Lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Historical records show that domesticated taro dispersed into China by 2200 years ago (Huang 2012). In the Near East, early historical descriptions of a crop that was termed Colocasia are available, leading some to suggest taro had reached Egypt from India by 300 BC and Italy by AD 200, known as Cyrenaic aron in Galen (Burkill 1938;Grimaldi et al 2018;Sallares 1991). Yet, in cases where this crop of antiquity has descriptions, they appear to refer to lotus rather than taro until the 2nd century AD (Grimaldi 2013;Watson 1983).…”
Section: Taromentioning
confidence: 99%
See 1 more Smart Citation
“…Historical records show that domesticated taro dispersed into China by 2200 years ago (Huang 2012). In the Near East, early historical descriptions of a crop that was termed Colocasia are available, leading some to suggest taro had reached Egypt from India by 300 BC and Italy by AD 200, known as Cyrenaic aron in Galen (Burkill 1938;Grimaldi et al 2018;Sallares 1991). Yet, in cases where this crop of antiquity has descriptions, they appear to refer to lotus rather than taro until the 2nd century AD (Grimaldi 2013;Watson 1983).…”
Section: Taromentioning
confidence: 99%
“…Accompanying historical records suggest the crop was already a local food and not traded through the port (van der Veen 2011). Other historical evidence verifies taro was widely grown along the Nile by AD 1000 (Grimaldi 2016;Grimaldi et al 2018; van der Veen and Morales 2017). It is far less certain when taro dispersed into sub-Saharan Africa, but genetic surveys of diversity suggest multiple introductions (Chaïr et al 2016).…”
Section: Taromentioning
confidence: 99%
“…In antiquity, Nicander of Colophon, Theophrastus, Dioscorides and later authors used this name (Greek Κολοκάσια) for the edible rhizomes of the Indian lotus or Egyptian bean ( Nelumbo nucifera ). However, after the 4 th century AD, a poorly understood semantic shift occurred and “Colocasia” became the name of the taro plant [42]. Once the Indian lotus fell out of use, Renaissance naturalists failed to associate the description of the Classical “Colocasia” with any of the plants known at the time.…”
Section: Resultsmentioning
confidence: 99%
“…Peaches ( Prunus persica (L.) Batsch) were introduced to Europe by the 1st century AD and peaches also have an Asian origin (Faust & Timon, 1995). Coincidentally, it has also recently been suggested that taro was introduced to Europe in the 4th century AD from south–eastern Asia (Grimaldi et al, 2018). Therefore, there are other examples of plants that have been transported between Asia and Europe for agriculture even before the 2nd millennium.…”
Section: Discussionmentioning
confidence: 99%